2014
DOI: 10.1007/s11121-014-0501-3
|View full text |Cite
|
Sign up to set email alerts
|

First Adaptation of Coping Power Program as a Classroom-Based Prevention Intervention on Aggressive Behaviors Among Elementary School Children

Abstract: Children with high levels of aggressive behavior create a major management problem in school settings and interfere with the learning environment of their classmates. We report results from a group-randomized trial of a program aimed at preventing aggressive behaviors. The purpose of the current study, therefore, was to determine the extent to which an indicated prevention program, Coping Power Program, is capable of reducing behavioral problems and improving pro-social behavior when delivered as a universal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…A previous randomized trial of CP with elementary school students has shown significant impacts on these children's behaviours both at post-intervention and at 1-year follow up. 18 We could hypothesize that teachers evaluate these patterns of behaviours as typical of the preschool age and/or that nursery school children have more opportunities to move during school activities compared with children in elementary school, and that this might help children to address their hyperactive difficulties naturally. The lack of an intervention effect in this domain may also reflect problems with the measures used to assess the construct.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous randomized trial of CP with elementary school students has shown significant impacts on these children's behaviours both at post-intervention and at 1-year follow up. 18 We could hypothesize that teachers evaluate these patterns of behaviours as typical of the preschool age and/or that nursery school children have more opportunities to move during school activities compared with children in elementary school, and that this might help children to address their hyperactive difficulties naturally. The lack of an intervention effect in this domain may also reflect problems with the measures used to assess the construct.…”
Section: Discussionmentioning
confidence: 99%
“…From a prevention standpoint, it is important that the current findings are consistent with those from prior researches on the outcomes of the targeted and universal prevention versions of CP. 16,18 In Italy, schools usually cater for both nursery and elementary levels; in this context, a multi-tiered prevention model can be delivered so that teachers, educators and/or school psychologists can learn a set of intervention skills and then flexibly deliver them to address preschooler or school-aged children's behavioural difficulties. These multiple levels of intervention could be considered a cost-effective procedure in school settings, reducing the expenditure of resources that might otherwise be dedicated to the adoption of multiple programmes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coping Power was and is being developed for use in different settings (Lochman et al 2012a;Muratori et al 2014). Previous studies have examined its use with Oppositional Defiant Disorder and Conduct Disorder in outpatient child clinics Van de Wiel et al 2007).…”
Section: Treatmentmentioning
confidence: 99%